Evaluation of Serum Inflammatory Markers and Their Relationship to Treatment Response in Alopecia Areata Patients - Icim Komurcugil; Nermin Karaosmanoğlu (Mattioli1885, 2024)
Introduction: Alopecia areata is a type of non-scarring alopecia, which is thought to be associated with T-cell mediated immune response. Objective: This study aims to compare the levels of serum inflammatory markers before and after treatment in patients with alopecia areata. The study will explore the utility of the systemic immune-inflammation index (SII) in assessing the severity and treatment response in alopecia areata patients. Methods: The study included 60 alopecia areata patients and 40 control patients diagnosed with tinea unguium, aged between 18 and 65 years. Sociodemographic characteristics such as age, gender, and medical history were recorded for both groups. For alopecia areata patients, serum inflammatory markers were recorded before and at the third month of treatment. Serum inflammatory markers for the control group were also recorded. Furthermore, the Severity of Alopecia Tool (SALT) score was calculated for alopecia areata patients before and at the third month of treatment. Results: The alopecia areata group had a significantly higher neutrophil-lymphocyte ratio, mean platelet volume, and SII values compared to the control group, while high-density lipoprotein (HDL) values were significantly lower. Serum inflammatory markers, assessed at the third month of treatment in the alopecia areata group, were lower and HDL values were significantly higher compared to pre-treatment levels. A statistically significant correlation was observed between disease severity and the SII. Conclusion: The SII is a cost-effective marker that can be utilized in assessing the severity of alopecia areata and treatment response.